THE EFFECTIVENESS OF IMPLEMENTING SUSTAINABLE DEVELOPMENT EVENTS IN PROMOTING ENVIRONMENTALLY FRIENDLY BEHAVIOR CHANGE: A QUANTITATIVE DESCRIPTIVE SYNTHESIS OF INTERNATIONAL CASE STUDIES - Linda Puspita Sari (RADJA PUBLIKA, 2026)
This study examines the effectiveness of Sustainable Development Events (SDEs) in promoting Pro-Environmental Behavior Change (PEBC) through a quantitative descriptive synthesis of several international case studies, including the Toronto International Film Festival (TIFF), Munich Streetlife Festival (SLF), Helsinki World Design Capital (WDC), and the Salt Lake Olympics. Using the Triple Bottom Line (TBL) framework combined with behavioral theories such as the Theory of Planned Behavior (TPB) and the Transtheoretical Model (TTM), the analysis explores how socio-cultural, environmental, and governance dimensions influence behavioral outcomes. The findings reveal that SDEs are particularly effective in reinforcing existing pro-environmental behaviors among motivated individuals, especially those in the Action Stage of behavioral change. Events also contribute to long-term sustainability through soft legacy development, such as institutional policy integration and governance transformation, as demonstrated in the Helsinki WDC case. Moreover, strong socio-cultural capital generated through community pride and social engagement creates a supportive normative environment that facilitates sustainable behavior adoption. However, the study identifies an “efficacy gap,” indicating that while SDEs successfully reinforce behavior among committed participants, they are less effective at initiating behavioral change among less motivated audiences. Overall, SDE effectiveness depends on the integration of socio-cultural engagement, strategic governance legacy, and targeted communication strategies to support long-term behavioral transformation.